CHOICE OF A RATIONAL TYPE OF VIBRATION GENERATOR FOR INERTIAL EXPLOSION GRATES - POLISHCHUK, LEONID; KUDRASH, VITALY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Casting is one of the most common methods of producing workpieces in the machine building and other industries. In particular, sand mold casting is the most common method for ferrous and non-ferrous metals. This casting method requires subsequent knocking out of the castings from the molds and pans, which is a complex technological operation that requires the use of various types of appropriate vibrating equipment, including inertial knockout grids. Automation and continuous development of production sets tasks for the modernization of vibrating equipment and the development of new design solutions, taking into account the possibility of ensuring the required operating modes, specific operating conditions, requirements for durability, reliability, maintainability and safety of use. An important structural element of vibration equipment is vibration exciters, which determine the efficiency of the process of extracting castings from the molds. The paper analyzes the known technical solutions of vibration exciters dedicated to solving this problem and identifies the main directions for improving the design of vibration exciters, as well as problems that require finding effective solutions. Typical designs are considered and the most common types of vibration equipment for knocking out castings are analyzed. The main types of vibration exciter drives used in inertial knockout screens depending on the specifics of production are identified. These are eccentric, cam, unbalanced, pneumatic and electromagnetic. The article analyzes the designs of vibration exciters and their drives and identifies the main advantages and disadvantages. It is concluded that it is necessary and expedient to reduce the weight and simplify the designs, expand the range of operating modes of these drives. It is proposed to use a hydraulic drive of the vibration exciter, which will improve the characteristics of inertial knockout gratings, provide the ability to work with pre- and post-resonance frequencies, expand the range of operating amplitudes and increase the range of processed molds. The expediency and prospects of developing new technological equipment, in particular, hydraulically driven vibration exciters, are indicated.
Keywords: vibrating exciter; vibrations; knockout grid; hydraulic drive; mold; casting